In Vitro Digestibility Evaluation of Cotton Stalk Treated with Different Substrate Based Fiber Degrading Liquid Enzymes at Varying Duration - S. F. Nipane (Indian Journal of Animal Nutrition, 2024)
The present study was made to evaluate the effect of fiber degrading liquid enzymes solution at different dilutions and duration on in vitro dry matter digestibility of cotton stalk. The cotton stalk was treated with rice straw, untreated cotton stalk and ozone treated cotton stalk substrate based liquid fibrolytic enzymes with 4 lit/kg (2 lit of extracted enzyme and 2 lit of water per kg substrate) for 24, 48, 72 and 96 hr soaking period. Liquid fibrolytic enzymes extraction, purification, characterization and standardization, enzyme activity, and application dosage optimization for substrate was carried out in Department of Chemical Engineering, Visvesvaraya National Institute of Technology, Nagpur. The treated substrates with different dilutions and durations were in vitro incubated to ascertain their effect on digestibility. The results revealed significant differences (p<0.01) in vitro of dry matter digestibility (%) of cotton stalk treated with ozone treated cotton stalk based followed by rice straw based liquid fibrolytic enzyme solution @ 4 lit/kg for 24 h soaking period and in untreated cotton stalk based liquid firbrolytic enzyme solution for 48 and 72 h soaking period. IVNDFD and IVADFD (%) higher in ozone treated cotton stalk based liquid fibrolytic enzyme treated cotton stalk as compare other substrate based enzymes. On conclusion, in vitro dry matter, neutral detergent fiber and acid detergent fiber digestibility (%) of cotton stalk treated with ozone treated cotton stalk based liquid fibrolytic enzymes were significantly higher (p<0.01) as compare to untreated cotton stalk and rice straw based treated cotton stalk.